Florid Cemento-Osseous Dysplasia-Associated Simple Bone Cyst Showing Marked Irregular Border and High Apparent Diffusion Coefficient Value - Ikuho Kojima; Takashi Nishioka; Maya Sakamoto; Yuko Sai; Yushi Ezoe; Masahiro Iikubo; Hiroyuki Kumamoto; Tetsu Takahashi (Case Reports in Dentistry)
A simple bone cyst (SBC) is an intrabone cavity without epithelial lining, which occasionally occur with fibrous-osseous lesions. The imaging finding of the scalloped border and conserving the lamina dura, periodontal ligament spaces, or follicular spaces are considered radiographically pathognomonic of SBC. SBC has been reported to occur with fibrous-osseous lesions, including cemento-osseous dysplasia (COD). Computed tomography (CT) imaging findings are sparse, and there are no reports of magnetic resonance imaging (MRI) findings, including apparent diffusion coefficient (ADC) value calculated by diffusion-weighted MRI for the florid COD-associated SBC. We report a case of a 39-year-old woman who was referred to our hospital because a panoramic radiograph of her right mandible showed asymptomatic radiolucency in the apical molar area. CT images showed a low-density lesion in the periapical areas of the right mandible, which accompanied a well-defined, high-density lesion, and a mixed low/high-density lesion with an unusual marked irregular border in the left mandible. The MRI showed cyst-like extremely hyperintense signals on fat-suppressed T2-weighted images at the right mandibular low-density and the left mandibular mixed low/high-density areas. ADC map showed high values (over 2.5×10−3 mm2/s) at the cystic areas in the bilateral mandible. We performed incisional biopsies of the bilateral mandibular lesions and resections of the bilateral maxillary lesions. Surgical and histopathological findings established a diagnosis of florid COD in the bilateral mandible and maxilla, simultaneously complicated by multiple SBCs in the bilateral mandible. The ADC value of cystic component is useful for the diagnosis, if the COD-associated SBC exhibits solitary, nonspecific, or rare imaging findings.